Pengaruh Keputusan Investasi, Pendanaan, dan Kebijakan Dividen terhadap Nilai Perusahaan pada Perusahaan Manufaktur di BEI 2020 – 2022 - Bagus Kusuma Ardi; Batista Sufa Kefi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine the effect of investment decisions, funding decisions, and dividend policies on firm value in food and beverage companies listed on the Indonesia Stock Exchange. The population in this study is 34 companies that are included in the food and beverage sector which are listed on the Indonesia Stock Exchange in 2020-2022. The sampling technique used is purposive sampling with certain criteria, so that the final sample that can be used is 13 companies. Research results obtained using SPSS version 17. The results of the study using the F test showed that the Fcount was 11.503> he F table was 3.267 with a significant value of 0.000 0.05 and it could be concluded that simultaneously it was accepted. The results of ui t calculate the investment decision (X1) of 4.673 > 2.030 and a significant value of 0.000 <0.050, t calculate the funding decision (X2) of 2.034 > 2.030 and a significant value of 0.050 <0.050, and t calculate the dividend policy (X3) of -0.484 <2.030 and a significant value of 0.631 0.050. This shows that X1 and X2 have an effect and are significant while X3 has no effect and is not significant on the value of the Company.